The future of continental philosophy of religion - Crockett, Clayton; Putt, B. Keith; Robbins, Jeffrey W. (Indiana series in the philosophy of religion, 2014)
Introduction: back to the future / Clayton Crockett, B. Keith Putt, and Jeffrey W. Robbins -- PART I. THE MESSIANIC -- Is continental philosophy of religion dead? / John D. Caputo -- Friends and strangers/poets and rabbis: negotiating a "Capuphalian" philosophy of religion / B. Keith Putt -- Response / Merold Westphal -- Response / John D. Caputo -- On faith, the maternal, and postmodernism / Edward F. Mooney -- The persistence of the trace: interrogating the gods of speculative realism / Steven Shakespeare -- Speculating God: speculative realism and Meillassoux's divine inexistence / Leon Niemoczynski -- Between deconstruction and speculation: John D. Caputo and A/Theological materialism / Katharine Sarah Moody -- PART II. LIBERATION -- The future of liberation / Philip Goodchild -- Monetized philosophy and theological money: uneasy linkages and the future of a discourse / Devin Singh -- "Between justice and my mother": reflections on and between Levinas and Žižek / Gavin Hyman -- Verbis indisciplinatis / Joseph Ballan -- Overwhelming abundance and everyday liturgical practices: for a less excessive phenomenology of religious experience / Christina M. Gschwandtner -- Countercurrents: theology and the future of continental philosophy of religion / Noëlle Vahanian -- PART III. Plasticity -- The future of Derrida: time between epigenesis and epigenetics / Catherine Malabou -- On reading--Catherine Malabou / Randall Johnson -- Necessity as virtue: on religious materialism from Feuerbach to Žižek / Jeffrey W. Robbins -- Plasticity in the contemporary Islamic subject / John Thibdeau -- From cosmology to the first ethical gesture: Schelling with Irigaray / Lenart Škof -- Prolegomenon to thinking the reject for the future of continental philosophy of religion / Irving Goh -- Entropy / Clayton Crockett